Persistent pupillary membrane: a rare case and its surgical management - Kumar Biswas, Sujit; Chowdhury, Nasimul Gani; Alam, Mahbubul; Roy, Soma Rani; Bhuiyan, Abdul Matin; Noor, Zubaida (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2023)
Aim: To discuss the surgical outcome of the persistent pupillary membrane (PPM), which is a rare entity. Case report: A female child aged seven and a half years has been reported to have had reduced vision in her right eye since birth. Her vision was counting fingers; after pupillary dilation, her vision improved to 6/24. A supranasal incision in the cornea was constructed under general anesthesia with a keratome of 3.2 mm size. A dispersive viscoelastic substance was introduced into the anterior chamber. The strands were excised with an iris scissor from their junction at the collarette. The viscoelastic material was removed, and a suture was placed. The post-operative patient was treated with cycloplegic, moxifloxacin, and dexamethasone eye drops. The pre- and post-operative periods were uneventful. After one and a half months, the patient’s vision improved to 6/9 with a refraction +0.50 DS with +1.00 Cyl at 1100. Conclusion: Pupilloplasty with excision of iris strands of PPM is relatively a safe procedure and might improve visual acuity.